2011
DOI: 10.1007/s00467-011-1833-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated systolic blood pressure in preterm very-low-birth-weight infants ≤3 years of life

Abstract: Preterm, very-low-birth-weight neonates (≤1500 gm, VLBW) exhibit elevated systolic blood pressures (SBP) in adolescence and adulthood; however, the age of onset and causes are unknown. We assessed SBP in a cross-sectional study of VLBW infants at 1, 2 and 3 years of age (n = 40 per cohort). SBP was manually measured using Doppler amplification (observed), and calm values were compared to reference ranges used for clinical purposes (expected). SBP was converted to age-, gender- and height-specific z-scores (SBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 32 publications
3
25
1
Order By: Relevance
“…The present study confirms this association in early childhood in VLBW infants and supports the hypothesis that programming of the HPA axis may contribute to the high prevalence of raised blood pressure in this population (9,10). The correlation between cortisol and both systolic and diastolic blood pressure was significant only in boys.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study confirms this association in early childhood in VLBW infants and supports the hypothesis that programming of the HPA axis may contribute to the high prevalence of raised blood pressure in this population (9,10). The correlation between cortisol and both systolic and diastolic blood pressure was significant only in boys.…”
Section: Discussionsupporting
confidence: 90%
“…We recently showed that at the corrected age of 2 y verylow-birth-weight (VLBW) infants (birth weight <1,500 g) have a high prevalence of raised blood pressure (systolic and/or diastolic ≥ 90th percentile for age, sex, and height) (9). Elevated blood pressure (compared to published reference standards) in early childhood in VLBW infants was also reported by Duncan et al (10).…”
mentioning
confidence: 58%
“…Studies have shown that blood pressure is lower in preterm infants born at 28-32 weeks GA and studied longitudinally across the first six months after term CA compared to age matched term infants in both active sleep and quiet sleep (Witcombe et al, 2008). In contrast when awake a recent study has reported that systolic blood pressure in VLBW infants was elevated at one year of age compared to published reference values when adjusted for age, gender and height (Duncan et al, 2011). These findings suggest that the elevated blood pressure reported in adolescence and adulthood born preterm appears as early as the first year of life.…”
Section: Heart Rate and Blood Pressure After Preterm Birthcontrasting
confidence: 53%
“…These findings suggest that the elevated blood pressure reported in adolescence and adulthood born preterm appears as early as the first year of life. Furthermore, there was no age related rise in blood pressure between one and three years of age (Duncan et al, 2011). In summary, it appears that heart rate and blood pressure are altered after preterm birth and these differences persist across the first year after term CA.…”
Section: Heart Rate and Blood Pressure After Preterm Birthmentioning
confidence: 94%
“…Understanding the childhood roots of these enduring differences is crucial, particularly within at-risk samples of low-birth-weight and premature children (3,4). Premature birth is associated with elevated blood pressure beginning in infancy and early childhood (5,6), which in turn is a risk factor for adult hypertension, heart disease, and early mortality (7,8). Black/African-American (AA) infants are approximately twice as likely to be born premature as white/European-American (EA) infants (9) and consequently are at greater risk for a wide range of adult health problems (10).…”
mentioning
confidence: 99%